Sensitive Measurement of Thrombopoietin by a Monoclonal Antibody Based Sandwich Enzyme-linked Immunosorbent Assay - Folman, Claudia C; von dem Borne, Albert E G K; Rensink, Irma H J A M; Gerritsen, Winald; van der Schoot, C Ellen; de Haas, Masja; Aarden, Lucien (Thrombosis and Haemostasis, 1997)
In this report a sensitive enzyme-linked immunosorbent assay (ELISA) for the measurement of plasma thrombopoietin (Tpo) is described that is solely based on monoclonal antibodies (MoAbs).The assay has an intra and inter-assay variance of 5-7% and 7-13%, respectively. Native and recombinant human Tpo (rhTpo) were recognized equally well, no cross reactivity with other cytokines was found and rhTpo added to plasma and serum was completely recovered. With the ELISA, Tpo concentrations in EDTA-anticoagulated plasma of all controls (n = 193) could be determined, since the limit of detection (2 ± 0.8 A.U./ml, mean ± sd) was lower than the concentration found in controls (11 ± 8 A.U./ml, mean ± sd; 2.5th-97.5th percentile: 4-32 A.U./ml). Tpo levels in serum were on average 3.4 times higher than in plasma.We showed in vivo that Tpo is bound by platelets, as in thrombocytopenic patients (n = 5) a platelet transfusion immediately led to a drop in plasma Tpo level, whereas in patients receiving chemotherapy the induced thrombocytopenia was followed by a rise in plasma Tpo levels.In summary, these results indicate that this ELISA is a reliable tool for Tpo measurements and is applicable for large scale studies.